Genet dynamics of a regenerating dwarf bamboo population across heterogeneous light environments in a temperate forest understorey. Issue 3 (8th January 2018) - Matsuo, Ayumi; Tomimatsu, Hiroshi; Sangetsu, Yushin; Suyama, Yoshihisa; Makita, Akifumi
Abstract: Despite the advantage of plant clonality in patchy environments, studies focusing on genet demography in relation to spatially heterogeneous environments remain scarce. Regeneration of bamboos in forest understoreys after synchronous die‐off provides an opportunity for assessing how they come to proliferate across heterogeneous light environments. In a Japanese forest, we examined genet demography of a population of Sasa kurilensis over a 7‐year period starting 10 years after die‐off, shortly after which some genets began spreading horizontally by rhizomes. The aboveground biomass was estimated, and genets were discriminated in 9‐m 2 plots placed under both canopy gaps and closed canopies. Overall, the results suggest that the survival and spread of more productive genets and the spatial expansion of genets into closed canopies underlie the proliferation of S. kurilensis . Compared to canopy gaps, the recovery rate of biomass was much slower under closed canopies for the first 10 years after the die‐off, but became accelerated during the next 7 years. Genet survival was greater for more productive genets (with greater initial number of culms), and the spaces occupied by genets that died were often colonized afterward by clonal growth of surviving genets. The number of genets decreased under canopy gaps due to greater mortality, but increased under closed canopies where greater number of genets colonized clonally from outside the plots than genets died. The colonizing genets were more productive (having larger culms) than those originally germinated within the plots, and the contribution of colonizing genets to the biomass was greater under closed canopies. Our study emphasizes the importance of investigating genet dynamics over relevant spatiotemporal scales to reveal processes underlying the success of clonal plants in heterogeneous habitats. Abstract : Despite the advantage of plant clonality in patchy environments, studies focusing on genet demography in relation to spatially heterogeneous environments remain scarce. Regeneration of bamboos in forest understoreys after synchronous die‐off provides an opportunity for assessing how they come to proliferate across heterogeneous light environments. We studied the long‐term genet demography of a dwarf bamboo, Sasa kurilensis, after synchronous flowering and die‐off, and found that the survival and spread of more productive genets and the clonal expansion of genets into closed canopies likely underlie the proliferation of S. kurilensis .